2020
DOI: 10.1109/access.2020.3036572
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Student Performance and Its Influential Factors Using Hybrid Regression and Multi-Label Classification

Abstract: Understanding, modeling, and predicting student performance in higher education poses significant challenges concerning the design of accurate and robust diagnostic models. While numerous studies attempted to develop intelligent classifiers for anticipating student achievement, they overlooked the importance of identifying the key factors that lead to the achieved performance. Such identification is essential to empower program leaders to recognize the strengths and weaknesses of their academic programs, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 53 publications
0
35
0
1
Order By: Relevance
“…Prediction accuracy of student academic performance requires an deep understanding of the factors and features that impact student results and the achievement of student (Alshanqiti & Namoun, 2020). For this purpose, Hellas et al (2018) reviewed 357 articles on student performance detailing the impact of 29 features.…”
Section: Literaturementioning
confidence: 99%
“…Prediction accuracy of student academic performance requires an deep understanding of the factors and features that impact student results and the achievement of student (Alshanqiti & Namoun, 2020). For this purpose, Hellas et al (2018) reviewed 357 articles on student performance detailing the impact of 29 features.…”
Section: Literaturementioning
confidence: 99%
“…Instead, it should be studied within a broader context, particularly using the student outcomes, which are now guiding the learning process by looking at the cohort performance. Moreover, recent research recommends exploring the prospect of predicting the attainment of student outcomes to infer student performance [29].…”
Section: Student Performancementioning
confidence: 99%
“…Learning analytics and educational data mining (i.e., EDM) are proclaimed to improve the attainment of student learning outcomes [108]. There are also several calls for automating the assessment of student outcomes, which represent a proxy for student performance and success [9,29]. However, it is unclear how student outcomes are modeled and predicted at the course and program level using data mining and machine learning models.…”
Section: Key Findingsmentioning
confidence: 99%
“…However, the quality of the Thai education has been found ineffective in terms of LOs, skill gap, and skills deficiencies, especially in the engineering disciplines [4,13,33]. Studies indicated that students' LOs are determined by several factors, including both academic and non-academic aspects [38], and there are two major limitations in the previous studies. Firstly, although most studies have shown a close relationship between WIL and LOs, few studies have explored the impact of WIL, psychology and learning factors on engineering students' LOs.…”
Section: Problem Statementmentioning
confidence: 99%